Effect of silica nanoparticles in kenaf reinforced epoxy: flexural and compressive properties - Bajuri, Farid; Mazlan, Norkhairunnisa; Ishak, Mohamad Ridzwan (Universiti Putra Malaysia Press, 2017)
Kenaf natural fibre is used as a sustainable form of material to reinforce polymeric composite. However, natural fibres usually do not perform as well as synthetic fibres. Silica nanoparticle is a material with high surface area and its high interfacial interaction with the matrix results in its improvement. In this research, silica nanoparticles were introduced into epoxy resin as a filler material to improve the mechanical properties of the kenaf-reinforced epoxy. They were dispersed into the epoxy using a homogeniser at 3000 rpm for 10 minutes. The composites were fabricated by spreading the silica filled epoxy evenly onto the kenaf mat before hot pressing the resin wet kenaf mat. The results show for flexural properties, composites with higher fibre and silica volume content generally had better properties with specimen 601 (60 vol% kenaf and1 vol% silica) having the highest strength at 68.9 MPa. Compressive properties were erratic with specimen 201 (20 vol% kenaf and 1 vol% silica) having the highest strength at 53.6 MPa.